2012
DOI: 10.1002/cbf.2923
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase and cytokine expression in Tenon fibroblasts during scar formation after glaucoma filtration or implant surgery in rats

Abstract: Failure of surgery for glaucoma is usually due to post-surgical scarring (fibrosis), a process in which fibroblasts play a prominent role. We investigated the molecular mechanisms of such scarring by examining the expression of matrix metalloproteinases and cytokines in Tenon fibroblasts isolated from rats after glaucoma surgery. Filtration surgery was performed in one eye and implant surgery in the other; and Tenon fibroblasts were isolated from the tissue surrounding the bleb after surgery. The cells were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The latter bind reversibly to the active site of MMPs in a 1:1 molar ratio and, pathological imbalances in this system have been linked to the pathogenesis of hepatic fibrosis [ 17 , 18 ]. It has also been shown that the levels of TIMPs increase significantly by TGF-β, IL-6 and IL-22 in several in vitro and in vivo studies [ 16 , 50 , 51 ]. Alternately, treatment with IL-10 has been demonstrated to significantly increase the production of MMPs, including MMP-9, as well as significantly decrease TIMPs during liver fibrosis [ 7 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latter bind reversibly to the active site of MMPs in a 1:1 molar ratio and, pathological imbalances in this system have been linked to the pathogenesis of hepatic fibrosis [ 17 , 18 ]. It has also been shown that the levels of TIMPs increase significantly by TGF-β, IL-6 and IL-22 in several in vitro and in vivo studies [ 16 , 50 , 51 ]. Alternately, treatment with IL-10 has been demonstrated to significantly increase the production of MMPs, including MMP-9, as well as significantly decrease TIMPs during liver fibrosis [ 7 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell-mediated tissue contraction is a complex process that involves various cellular activities, including cell migration and reorganisation of the extracellular matrix, and MMPs have been implicated in wound contraction and matrix reorganisation 17. MMPs play a central role in collagen contraction and their overexpression is associated with excessive scarring at the ocular surface 18. Inhibition of MMPs was shown to limit subconjunctival scarring after experimental glaucoma filtration surgery in rabbits 19.…”
Section: Discussionmentioning
confidence: 99%
“…According to the available literature, there are some protocols for primary Tenon’s fibroblast isolation [4, 5, 14]. Most papers present effective isolation of Tenon’s fibroblasts or trabecular meshwork cells using a complicated collagenase digestion method [1, 5] with basal culture media such as MEM [15], DMEM [1, 4, 14, 16] or RPMI-1640 [4, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Most papers present effective isolation of Tenon’s fibroblasts or trabecular meshwork cells using a complicated collagenase digestion method [1, 5] with basal culture media such as MEM [15], DMEM [1, 4, 14, 16] or RPMI-1640 [4, 17]. According to these protocols, successful HTF isolation requires long-term culture of the tissue explants: approx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation